Political Education as a Catalyst for Adaptive Social Transformation Based on Structural Functional Theory (Durkheim & Parsons): Pendidikan Politik sebagai Katalis Transformasi Sosial Adaptif Berbasis Teori Struktural Fungsional (Durkheim & Parsons) - Azmi, Diinu Tsabitul (SiRad: Pelita Wawasan, 2025)
Contemporary dynamics characterized by globalization, the information technology revolution, and shifting values ​​have the potential to trigger socio-political complexity and polarization. In this context, political education is crucial as a central socialization tool that shapes participatory and responsible citizens, serving as the foundation for a stable political system. This research aims to examine and analyze how political education acts as a catalyst for constructive and integrated social transformation, applying Structural Functional Theory (Durkheim & Parsons) to understand its adaptive function. A qualitative methodology through a comprehensive literature review was used, analyzing various scientific publications to identify patterns and implications for the role of political education. Initial findings indicate that political education contributes to social transformation through the socialization of democratic values, the formation of adaptive change agents, and the strengthening of institutional legitimacy. This enables society to adapt evolutionary without fundamental disruption. The novelty of this research lies in the systematic integration of the role of political education as an agent of social transformation with an explicit Structural Functional Theory lens, aimed at enhancing understanding of the processes of political institutions and strengthening their legitimacy and public trust. Therefore, this approach offers a fresh perspective on the contribution of educational institutions to functional health and sustainability within social systems through the integrative perspectives of Durkheim and Parsons. [Dinamika kontemporer yang diwarnai globalisasi, revolusi teknologi informasi, dan pergeseran nilai sangat berpotensi memicu kompleksitas sosial-politik serta polarisasi. Dalam konteks ini, pendidikan politik sangat krusial sebagai sentral sosialisasi yang membentuk warga negara partisipatif dan bertanggung jawab, sebagai fondasi stabilitas sistem politik. Penelitian ini bertujuan mengkaji dan nmenganalisis bagaimana pendidikan politik berperan sebagai katalisator transformasi sosial yang konstruktif dan terintegrasi, dengan mengaplikasikan Teori Struktural Fungsional (Durkheim & Parsons) untuk memahami fungsi adaptifnya. Metodologi kualitatif melalui studi literatur komprehensif digunakan, menganalisis beragam publikasi ilmiah untuk mengidentifikasi pola dan implikasi peran pendidikan politik. Temuan awal mengindikasikan bahwa pendidikan politik berkontribusi pada transformasi sosial melalui sosialisasi nilai-nilai demokratis, pembentukan agen perubahan yang adaptif, serta penguatan legitimasi institusi. Ini memungkinkan masyarakat beradaptasi secara evolusioner tanpa disrupsi fundamental. Kebaruan penelitian terletak pada integrasi sistematis antara peran pendidikan politik sebagai agen transformasi sosial dengan lensa Struktural Fungsional secara eksplisit sebagai upaya meningkatkan pemahaman terhadap proses terhadap institusi politik, serta memperkuat legitimasi dan kepercayaan publik, oleh karenanya Pendekatan ini menawarkan perspektif segar mengenai kontribusi institusi pendidikan terhadap kesehatan fungsional dan keberlanjutan dalam sistem sosial melalui pandangan integratif Durkhem dan Parsons.]